Perinatal Complications in Twin Pregnancies after 34 Weeks: Effects of Gestational Age at Delivery and Chorionicity - Vergani, Patrizia; Russo, Francesca Maria; Follesa, Ilaria; Cozzolino, Sabrina; Fedeli, Tiziana; Ventura, Luisa; Ghidini, Alessandro (American Journal of Perinatology, 2013)
Objective To evaluate the perinatal outcome of twins approaching term in relation to chorionicity and gestational age at delivery.Study Design We accessed data pertaining to a cohort of 471 twin pregnancies with certain chorionicity delivered at > 34.0 weeks' gestation. Twin gestation per se, estimated fetal weight below the 10th percentile, or any intertwin discordance was not an indication for delivery before 40.0 weeks. Predictors of adverse perinatal outcome were identified using logistic regression analysis.Results There were no stillbirths. Adverse neonatal outcome occurred in 27% of monochorionic versus 16% of dichorionic gestations. At multivariate analysis, lower gestational age at delivery (odds ratio [OR] 0.70, 95% confidence interval [CI] 0.57 to 0.87), monochorionicity (OR 2.06, 95% CI 1.16–3.63), and either twin being growth-restricted (OR 2.35, 95% CI 1.22 to 4.54) were independent predictors of adverse neonatal outcome. Analysis of adverse neonatal outcome stratified by gestational age and chorionicity identified 36 to 37 weeks as optimal timing for delivery of monochorionic twins, and dichorionic twin pregnancies should be allowed to continue until term.Conclusion Among twin gestations delivered after 34 weeks with appropriate fetal growth, reassuring fetal status at weekly assessment, and absence of obstetric complications, delivery after 36 weeks for monochorionic twins and at term for dichorionic twins minimizes the risk of stillbirths and neonatal morbidity.
Keywords: twins; chorionicity; delivery; neonatal outcome